Case Report: Successful Treatment of Acute Generalized Exanthematous Pustulosis With Secukinumab - Zhang, Liangliang; Xu, Qiuyun; Lin, Tingting; Ruan, Shifan; Lin, Mengting; Bao, Chengbei; Zhang, Jing; Liu, Tao; Gong, Ting; Ji, Chao (Frontiers in Medicine, 2021)
Acute generalized exanthematous pustulosis is a severe, usually drug-related reaction, characterized by an acute onset of mainly small non-follicular pustules on an erythematous base. Most cases of acute generalized exanthematous pustulosis (AGEP) clear quickly with a systemic corticosteroid, but severe or recalcitrant cases may need other systemic therapies. In this case, a man in his 40 s with a history of psoriasis consulted a physician about widespread erythema, pustules, target lesions, and fever after the administration of a quadruple antituberculosis drug. Routine laboratory testing revealed elevated white blood cell count and C-reactive protein. The histopathology showed subcorneal pustules, spongiosis as well as lymphocyte and eosinophils infiltration in the dermis. The patient was diagnosed with definitive AGEP according to the diagnostic score from the EuroSCAR study. Cutaneous lesions especially pustules and erythema multiforme-like lesions on the upper arms and palms are crucial for distinguishing AGEP from Generalized pustular psoriasis. The patient was treated with secukinumab as a result of his failure to respond to topical corticosteroids and constrain of systemic steroids. Remission with secukinumab therapy was safe without increased risks of infections. This case indicates that secukinumab is a potential therapy that can rapidly improve the clinical symptoms of AGEP.